2021
DOI: 10.1186/s12887-021-02795-w
|View full text |Cite
|
Sign up to set email alerts
|

Sleep disorders in a sample of Lebanese children: the role of parental mental health and child nutrition and activity

Abstract: Background Sleep habits are an important component of a child’s health and it is affected by parent–child relationship. Also, child’s diet and nutrition appear to be an important factor affecting sleep health. Few studies have addressed the effect of parental emotional disturbance that can leave on children’s sleep. Therefore, the objective of our study was to assess the prevalence of sleep disorders in pre- and school-aged children and evaluate its relation with parental mental health and chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 51 publications
1
2
0
1
Order By: Relevance
“…Consistent with previous studies, we found an association between parenting behaviors and children's emotional and behavioral problems [13][14][15][16]. And in this study, parents' hostile/coercive strategies have a more signi cant impact on children.…”
Section: Sample Characteristicssupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with previous studies, we found an association between parenting behaviors and children's emotional and behavioral problems [13][14][15][16]. And in this study, parents' hostile/coercive strategies have a more signi cant impact on children.…”
Section: Sample Characteristicssupporting
confidence: 91%
“…Parenting plays an important role in improving children's sleep [10,11], which can directly or indirectly in uence their children's sleep condition through speci c parenting style (authoritative, authoritarian, permissive, and uninvolved) [12]. Some studies have shown that parents' mood and parenting pressure can affect children's sleep quality [13][14][15]. Parental rearing behavior and poor sleep hygiene are also related to sleep di culties in normally developing children [16].…”
Section: Introductionmentioning
confidence: 99%
“…Ancak, Kanada'da 10-17 yaş arası çocuklarda yapılan çalışmada 24 Saatlik Aktivite Kılavuzu önerilerilerinden biri olan orta ila şiddetli fiziksel aktiviteye çocuk ve gençlerin ancak %35'inde ulaşıldığı raporlanmıştır (58). Sfeir ve arkadaşlarının Lübnan 'da yaptığı bir çalışmada, çocuklarda iyi uyku düzeyinin daha yüksek beslenme ve fiziksel aktivite puanları ile ilişkili olduğu bildirilmiştir (59)…”
Section: Bulgularunclassified
“…The pandemic and the Beirut port explosion came on top of a crushing economic crisis with the highest inflation rate the country has seen in over thirty years [23]. The Lebanese people are facing several mental issues as demonstrated in the latest body of research conducted in the country [24][25][26][27][28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%